(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to discuss the Whistleblowing System, Internal Control and Fraud Prevention. This type of research uses verification. The population is all unit leaders at PT. Bank BJB Bandung City as many as 31 unit leaders. Sampling using saturated samples because the population is 31 unit leaders. This study processed statistical data using multiple regression analysis which was analyzed using IBM SPSS 25. This study found that the whistleblowing system and Internal Control affect fraud prevention. This study provides insight into the unit leader to improve whistleblowing systems facilities and internal control based on the input and experience of individual performance in improving fraud prevention.